De los derechos de los grupos indígenas en el marco internacional (2021)
Based on a historical research method, a legislative review of the rights of indigenous people in the international framework is made, based on the recognition of socio-cultural diversity and the possible conflict that this constitutionally learned reality entails. The importance of the socio-cultural diversity of indigenous communities and their worldview in the face of practices that violate human dignity —such as female genital mutilation—, which are the current focus of interests of the international community, is discussed.